Naked playwriting : the art, the craft, and the life laid bare - Downs, William Missouri, 1955-; Russin, Robin U., 1957- (Los Angeles : Silman-James Press, 2004)
Offers a playwriting course, from developing a theme through plotting and structuring a play, developing characters, creating dialog, formatting the script, and applying methods that aid the actual writing and rewriting processes. This book also provides guidance on marketing and submitting play scripts for both contests and production.
Includes bibliographical references (pages 327-328) and index.
Keywords: Playwriting; Drama -- Marketing; Mercadeo de teatro; Teatro -- Técnicas; Dramaturgia